THE IMPACT OF HUMAN RESOURCE MANAGEMENT ON EMPLOYEES AND ORGANIZATIONAL PERFORMANCE: A REVIEW ARTICLE - Muhammad, Ramzan Ali; Ibtahaj, Ali (University Research Base, 2025)
Employee and organizational outcomes are significantly influenced by human resource management (HRM) strategies. The purpose of this study is to look into how HRM affects both organizational and personnel performance. The article identifies the key HRM practices such as hiring and selection, training and development, performance management, pay and benefits, and labor relations that have a positive or negative impact on employee and organizational performance through a thorough literature review. As a result, the study comes to the conclusion that effective HRM practices can enhance employee performance, commitment, and happiness as well as organizational performance, and they play a major role in the success of a business as a whole.